Do The Frail Experience More Adverse Events From Intensive Blood Pressure Control? A 2-Year Prospective Study In The Irish Longitudinal Study On Ageing (TILDA) - Romero-Ortuno, Roman; Kenny, Rose (My University, 2022)
Background: The 2018 European Society of Cardiology/European Society of Hypertension (ESC/ESH) guidelines for management of hypertension in adults aged ≥65 years recommend a blood pressure (BP) treatment target of 130–139/70–79 mmHg if tolerated. Randomised controlled trials have advocated for lower BP, but this may have adverse outcomes in the frail. Yet, definitions of frailty vary. Methods: Using a prospective, observational study design, we compared two frailty classifications in their ability to predict short-term adverse outcomes associated with intensive BP control (<130/70 mmHg) in The Irish Longitudinal Study on Ageing (TILDA). Data from participants aged ≥65 treated for hypertension in Wave 1 (W1) between October 2009 and June 2011 were analysed. Frailty was identified by Frailty Phenotype (FP) and the Clinical Frailty Scale (CFS). We formulated 8 participant groups based on frailty-BP combinations. Outcomes at wave 2 (W2) in 2012–2013 were analysed with adjusted binary logistic regression models. Findings: Of 1920 W1 participants aged ≥65 and treated for hypertension, 1229 had full BP/FP and 1282 BP/CFS data. While the FP only identified risk of hospitalisation associated with intensive BP treatment, intensively treated frail-by-CFS participants had no increased or decreased risk of adverse outcomes, but those treated above the target had a higher risk of falls/fractures. In the non-frail by FP, intensive blood pressure treatment was associated with reduced risk of falls/fractures. Interpretation: Different frailty classifications may have different prognostic implications for the purpose of the application of hypertension management guidelines. Our study had limited power due to low frailty prevalences, so further research is needed. Guidelines should specify the recommended frailty identification method/s. In the frail, therapy personalisation is needed.
PUBLISHED
Keywords: Ageing; Age-related disability; Chronic Health Condition; Mobility impairment; Physical disability; Stroke; Health